Rituximab–cyclophosphamide–dexamethasone combination in the management of autoimmune cytopenias associated with chronic lymphocytic leukemia - Rossignol, J; Michallet, A-S; Oberic, L; Picard, M; Garon, A; Willekens, C; Dulery, R; Leleu, X; Cazin, B; Ysebaert, L (Leukemia, 2011)
We report our experience on rituximab–cyclophosphamide–dexamethasone (RCD) combination therapy for the treatment of autoimmune disorders (AIDs) in 48 chronic lymphocytic leukemia (CLL) patients. Overall, 81% of patients were relapsing for AID after previous treatment with corticosteroids, splenectomy, rituximab or alemtuzumab. Diagnosis of AID was autoimmune hemolytic anemia (AIHA) in 26 (54%), autoimmune thrombocytopenia (AITP) in 9 (18.8%), Evan's syndrome in 8 (16.7%) and pure red cell aplasia (PRCA) in 5 patients (10.5%). Median time of autoimmune disorder (AID) onset from CLL diagnosis was 60 months (range: 0–240), and CLL was considered progressive in 40% of subjects upon AID diagnosis (complex AID). Median hemoglobin pre-treatment was 7.7 g/100 ml, and median platelet count 36.5 × 10 9 /l, returning to a median of 12.5 /100ml and 37.5 × 10 9 /l, respectively. Overall, an 89.5% response rate was obtained with this combination, irrespective of the AID type. Relapse occurred in 19 patients (39.6%). Median duration of response for autoimmunity (DR-AI) was 24 months, but DR-AI was higher for patients presenting: (1) AID early during CLL course (<3 years), or (2) both PRCA and AIHA. Median time to CLL progression in 48 patients was 16 months, but this time was statistically shorter for Evan's syndrome and AITP patients as compared with AIHA and PRCA patients. This study emphasizes the relevance of CLL-directed immune chemotherapy in the management of CLL-associated AID.